Influencia del clima organizacional en el rendimiento del personal en la empresa mannucci diesel s.a.c. en el año 2012 - Diaz Sanchez, Sheyla Elizabet (2013)
The organizational climate is a variable that reflects the interaction between personal and organizational characteristics, considered as a fundamental element in the perception that the worker has the structures and processes that occur in their work environment. Poe thus this report is to analyze the organizational climate in the company Mannucci Diesel SAC, proposing recommendations to help improve the perception that workers in this company organizational climate prevailing in your work area. To carry out this study we chose a questionnaire that includes the dimensions proposed by Palma Carrillo, Sonia 2004, First Edition. Lima Peru, to measure the organizational climate. The final sample size of 125 workers surveyed constituted. Based on the obtained results concludes that the working environment which is experienced in the analysis unit broadly is neutral, since 50% of the average perceived dimensions are evaluated on this scale (Embodiment Personal, Work Involvement, Oversight, Communication and Working Conditions), likewise, the overall average score corroborated. Chapter I is the theoretical framework, details the problematic reality, history, theoretical, conceptual framework, the scientific problem, assumptions and objectives, the Chapter II is the methodological framework: detailing the methods, techniques, instruments, and the sample population, in Chapter III defines the presentation, analysis and discussion of results, in Chapter IV presents the conclusions, in Chapter V the recommendations aimed at improving the working conditions and quality of life workers, in Chapter VI bibliographical references and annexes finally show.